The extraordinary optical transmission and sensing properties of Ag/Ti composite nanohole arrays. Issue 7 (1st February 2019) - Larson, Steven; Carlson, Daniel; Ai, Bin; Zhao, Yiping
Abstract : Ag/Ti composite nanohole arrays were fabricated through a combination of nanosphere lithography, reactive ion etching, and co-deposition. The sensing performances were improved by the tunable dispersion of the Ag/Ti composites. Abstract : Ag/Ti composite nanohole arrays are fabricated by a simple combination of nanosphere lithography, reactive ion etching, and dual e-beam deposition techniques. Based on the X-ray diffraction, conductivity, and ellipsometry measurements, there exists a Ag composition threshold C Ag = 80 at% above which Ag is percolated through the entire film. Significant extraordinary optical transmission (EOT) is observed in nanohole samples with composition larger than the threshold. The main EOT peak position, the (1, 0) Ag/glass resonance peak, redshifts as the C Ag value decreased, but its index sensitivity monotonically increased with C Ag till a value of 300 RIU nm −1 for the C Ag = 100 at% sample is achieved. However, the LSPR peak of the nanoholes can achieve a sensitivity of 390 nm RIU −1 when C Ag decreases from 100 at% to 85 at%. This study demonstrates that besides the shape, size, and measurement configuration, the resonances and sensitivities of nanohole arrays can be effectively predicted and tuned by the composition of a plasmonic composite.